Penentuan Kadar Protein dan Karbohidrat pada Limbah Batang Pohon Pisang Kepok (Musa paradisiaca normalis) - Dhamayanti, Noviasri; Tiwow, Vanny M. A.; Nuryanti, Siti (Jurnal Akademika Kimia, 2018)
The aim of this study was to determine protein and carbohydrate levels contained in waste of banana kepok (Musa paradisiaca Normalis) trees. Samples were taken from Mpanau Sigi Central Sulawesi. This study used Kjeldahl method in determining protein level, and anthrone method in determining reducing sugar level. The analysis results obtained in the hard layer of banana tree are 3.05% of protein level and 6.75% of carbohydrate level, while in the soft layer of banana tree are 0.08% of protein level and 4.75% of carbohydrate level, respectively. This study concluded that protein and carbohydrate levels obtained from the hard layer of banana kepok trees waste is higher, than literatures.